Evaluation of adjunct immunohistochemistry on reporting patterns of non-small cell lung carcinoma diagnosed histologically in a regional pathology centre. Issue 12 (23rd May 2011) - McLean, E C; Monaghan, H; Salter, D M; Wallace, W A
Abstract : Morphological sub-classification of non-small cell carcinoma in small biopsy specimens presents difficulties for pathologists and recent advances in chemotherapy have resulted in increased pressure to more robustly differentiate between squamous carcinoma and adenocarcinoma. The results of audits examining classification of non-small cell lung carcinoma by pathologists working in a specialist team within a regional centre and the effect of introducing adjunct immunohistochemistry into the reporting pathway are presented. It is concluded that the use of a limited immunohistochemical panel substantially reduces the number of cases when a specific cell type cannot be identified or 'favoured' (34% to 6%) and that the classification obtained correlates well with that found in subsequent resection specimens. In addition the introduction of immunohistochemistry substantially reduces the variability in reporting practice between pathologists.